Implementasi Analisis SWOT dalam Strategi Pemasaran Pembiayaan Murabahah Plus Pada Bank Nagari Syariah - Kurnia, Rahmat (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study aims to determine the implementation of SWOT analysis in the marketing strategy of murabahah plus financing at Bank Nagari Syariah Branch Batusangkar. This research is a qualitative descriptive approach. Data collection techniques were carried out through structured interviews. The data analysis technique uses data reduction, data presentation and conclusion drawing. The results showed that the marketing strategy carried out by Bank Nagari Syariah Branch Batusangkar using 4P as for the murabahah plus financing product, it is the flagship product at the Nagari Syariah Bank Batusangkar Branch, while the price for murabahah plus financing is that the margin is relatively competitive by following market prices. Furthermore, for the place that the bank is in a strategic location, while for the promotion the bank promotes murabahah plus products with advertising, sales, publicity, and direct sales